Imagining Korea: the Bush administration's framing of North and South Korea. - Teo, Sarah Li-Shan. (2013)
The process of reconciliation and reunification of the Korean peninsula has important implications for regional and global stability. Inter-Korean reconciliation affects, and is affected by the triangular relations among North Korea, South Korea and the US. This dissertation focuses on the prospects of inter-Korean reconciliation during the George W. Bush administration and argues that in its inter-Korean rhetoric and discourse, the US framed South Korea as an ally and partner against North Korea, while imagining the North as part of the “axis of evil and a threat to international security. I will use rhetoric from two events to illustrate my point - the 2001 US- South Korea summit and the 2004 US Presidential Elections campaign. In both case studies, three themes were evident in the Bush administration s rhetoric: the construction of an US-and-allies Self against a North Korean Other, the emphasis on the US' necessary presence in Northeast Asia, and the expression of skepticism over North Korea's intentions. This framing of North and South Korea as unalterable opposites impeded inter-Korean reconciliation during the Sunshine policy era.